2011
DOI: 10.1093/icesjms/fsr058
|View full text |Cite
|
Sign up to set email alerts
|

The advantages of an audit over a census approach to the review of video imagery in fishery monitoring

Abstract: Stanley, R. D., McElderry, H., Mawani, T., and Koolman, J. 2011. The advantages of an audit over a census approach to the review of video imagery in fishery monitoring. – ICES Journal of Marine Science, 68: 1621–1627. Technology-based fishery monitoring, or electronic monitoring (EM), has emerged as an alternative to human observers and is being applied in a variety of fisheries. The method records sensor and image data from fishing operations, so can be used to provide 100% monitoring of catches and fishing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 3 publications
0
17
1
Order By: Relevance
“…The results showed that, on an overall fleet level, there was a tendency for video inspectors to underestimate discards by 32% compared to fishers' discard estimates This supports the findings of Ulrich et al (2015) and van Helmond et al (2015), which suggest that, despite offering a promising way to supplement existing on-board observer control, the REM approach applied in this trial needs some adjustments to optimise video inspector accuracy. This is emphasised by the results obtained when removing all observations where video inspectors commented on the poor quality of the REM data, which showed an overall agreement between fishers and video inspectors on the discard estimates, thus supporting the findings of Stanley et al (2011) and Kindt-Larsen et al (2011). The high accuracy was also underpinned by the comparison between video inspectors and on-board observers, where there was a good overall agreement between the discards amounts in each haul.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The results showed that, on an overall fleet level, there was a tendency for video inspectors to underestimate discards by 32% compared to fishers' discard estimates This supports the findings of Ulrich et al (2015) and van Helmond et al (2015), which suggest that, despite offering a promising way to supplement existing on-board observer control, the REM approach applied in this trial needs some adjustments to optimise video inspector accuracy. This is emphasised by the results obtained when removing all observations where video inspectors commented on the poor quality of the REM data, which showed an overall agreement between fishers and video inspectors on the discard estimates, thus supporting the findings of Stanley et al (2011) and Kindt-Larsen et al (2011). The high accuracy was also underpinned by the comparison between video inspectors and on-board observers, where there was a good overall agreement between the discards amounts in each haul.…”
Section: Discussionmentioning
confidence: 60%
“…Many previous studies have evaluated REM to be largely reliable and accurate (Ames et al, 2007;Kindt-Larsen et al, 2011;Needle et al, 2015;Stanley et al, 2009Stanley et al, , 2011Ulrich et al, 2015;van Helmond et al, 2015). However, most previous studies included fisheries (such as hook and line fisheries) where it was easy to identify individual fish in the catch (Ames et al, 2007;McElderry et al, 2003) or only focused on a single species in a mixed fishery, usually cod (Gadus morhua) (Kindt-Larsen et al, 2011;van Helmond et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Additional costs are incurred to review video footage collected by onboard cameras. These costs could be kept in check through a system of fisherman self-reporting and random auditing (Stanley et al, 2011). That is, fines for misreporting bycatch coupled with random audits would likely be sufficient to ensure effective monitoring and thus implementation of a cap-and-trade bycatch management program.…”
Section: Resultsmentioning
confidence: 99%
“…Video-based electronic monitoring (EVM) has recently emerged as an effective alternative for observer coverage in some fisheries (Ames et al 2007;Stanley et al 2009). The cost of EVM implementation can be less than equivalent observer coverage (Stanley et al 2011). Electronic video monitoring is perhaps most cost effective when it is used as a tool to audit self-reported logbook data (Stanley et al 2011).…”
mentioning
confidence: 99%
“…The cost of EVM implementation can be less than equivalent observer coverage (Stanley et al 2011). Electronic video monitoring is perhaps most cost effective when it is used as a tool to audit self-reported logbook data (Stanley et al 2011). Satellite-based vessel monitoring systems (VMSs) (Deng et al 2005;Harrington et al 2007;Witt and Godley 2007;Lee et al 2010;Hintzen et al 2012;Jennings and Lee 2012;Russo et al 2014a) and even simple GPS data loggers (GPSDLs) (Marrs et al 2002;Gallaway et al 2003aGallaway et al , 2003b are also capable of effort accounting.…”
mentioning
confidence: 99%